2014
DOI: 10.1093/rheumatology/ket428
|View full text |Cite
|
Sign up to set email alerts
|

The association of cytokines with disease activity and damage scores in systemic lupus erythematosus patients

Abstract: Increased levels of a number of immunomodulatory cytokines relative to IL-12p70 in this Caucasian SLE patient population are seen in patients with renal involvement and are associated with increased accrual of damage at the 5-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
5
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 31 publications
7
56
5
4
Order By: Relevance
“…Li et al . indicated that linc0597 and linc0949 not only involved in innate immunity but also regulate the induction of proinflammatory cytokines like tumor necrosis factor (TNF)-α and interleukin (IL)-6 [35], both of which are implicated in SLE pathogenesis [3639]. However, linc0949, which is present at low levels in PBMCs of patients with SLE, shows no significant difference between total SLE patients and healthy controls in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Li et al . indicated that linc0597 and linc0949 not only involved in innate immunity but also regulate the induction of proinflammatory cytokines like tumor necrosis factor (TNF)-α and interleukin (IL)-6 [35], both of which are implicated in SLE pathogenesis [3639]. However, linc0949, which is present at low levels in PBMCs of patients with SLE, shows no significant difference between total SLE patients and healthy controls in our study.…”
Section: Discussionmentioning
confidence: 50%
“…The induction of these pro-inflammatory mediators is facilitated through the binding of high-mobility group box 1 protein, engagement of Toll-like receptor 2 (TLR-2) and receptor for advanced glycation end-products (RAGE), activation of the MAPK, protein kinase C (PKC), inhibitor of kappa-light chain-enhancer of activated B cells (IκB) and nuclear factor kappa B (NF-κB) signaling pathways, and endoplasmic reticulum stress 20, 3235 . Correlation between serum levels of IL-1β, IL-6, TNF-α, hyaluronan, and lipocalin and disease activity in patients with SLE further highlights the importance of these inflammatory markers in the pathogenesis of LN 17, 3639 .…”
Section: Recent Knowledge On Renal Inflammation In Lupus Nephritismentioning
confidence: 91%
“…These actions are initiated under the influence of IL-23, IL-17 and some other additional novel factors. The IL-23-IL-17 axis, rather than the loop of IL-12 and IFN-c, have a central role in the autoimmune inflammation, and interaction between IL-23 and IL-17 is not only essential for the onset phase, but also for the destruction phase of SLE characterized by the T cell-mediated activation of osteoclastogenesis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of single nucleotide polymorphisms (SNPs) in the genetic contribution to SLE still awaits extensive investigation. Moreover, the prevalence of SLE varies between ethnic groups and it is well established that patients from different genetic backgrounds have different disease severity and clinical phenotype [5]. Because, the IL-23/Th17 signaling pathway, consisting of IL-23/IL-23R and IL-17F encoding genes, might represents a candidate way for SLE pathogenesis with possible involvement in disease susceptibility, we decided to explore whether polymorphisms located in the IL-23A (703 G/A; rs11171806), IL-23R (rs1884444 G/T, rs10489629 G/A) and IL-17F (7488A/ G (His161Arg; rs763780) and 7383A / G (Glu126Gly; rs2397084)) genes are associated with SLE in a predominantly Polish population using case-control studies.…”
Section: Introductionmentioning
confidence: 99%